2016
DOI: 10.1684/epd.2016.0831
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences with tachycardia‐triggered vagus nerve stimulation using the AspireSR stimulator

Abstract: Many epilepsy patients treated with vagus nerve stimulation additionally use an “on‐demand” function, triggering an extra stimulation to terminate a seizure or diminish its severity. Nevertheless, a substantial number of patients are not able to actively trigger stimulations by use of a magnet, due to the absence of an aura or inability for voluntary actions in the early phase of a seizure. To address this need, a novel implantable pulse generator, the AspireSR VNS system, was developed to provide automated ic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
0
11
0
2
Order By: Relevance
“…In addition to the Normal Mode and the Magnet Mode, the Model 106 (AspireSR) obtained the AutoStim Mode to automatically deliver an additional stimulation, triggered by a cardiac-based seizure-detection algorithm (SDA). [32][33][34][35][36] Thence, the closed-loop system has been added to the primary open-loop system. The Model 106 always monitors heart rate, and determines the baseline heart rate as a moving average of the instantaneous heart rate over the previous 5 minutes and the foreground heart rate as a moving average of the most recent 10 seconds.…”
Section: Implantable Devices For Medically Refractory Epilepsymentioning
confidence: 99%
“…In addition to the Normal Mode and the Magnet Mode, the Model 106 (AspireSR) obtained the AutoStim Mode to automatically deliver an additional stimulation, triggered by a cardiac-based seizure-detection algorithm (SDA). [32][33][34][35][36] Thence, the closed-loop system has been added to the primary open-loop system. The Model 106 always monitors heart rate, and determines the baseline heart rate as a moving average of the instantaneous heart rate over the previous 5 minutes and the foreground heart rate as a moving average of the most recent 10 seconds.…”
Section: Implantable Devices For Medically Refractory Epilepsymentioning
confidence: 99%
“…Clinical research has shown that the AspireSR VNS system is effective in detecting IT and provides automated on-demand stimulation, and improves the sensitivity and specificity of ictal stimulations. 9 11 However, no studies have evaluated whether VNS therapy on patients with epilepsy who have ictal bradycardia (IB) or normal HR may be ineffective or less ineffective than on patients with IT. It is very important to screen out candidates who potentially will not benefit from VNS to avoid unnecessary, invasive procedures and to improve the overall clinical efficacy of VNS treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the tolerability of additional tachycardia-based stimulation was good in this report, and two out of three patients showed an improvement in seizure frequency. 9 Hampel et al has reported a sensitivity of 92% and a specificity of 13.5% for the seizure detection algorithm in a single patient and has also reported a significant decrease in seizure duration as a result of closed-loop VNS with the AspireSR. 11 In addition, a prospective multicenter study of cardiac-based seizure detection to activate VNS demonstrated the ability to detect seizures based on cardiac changes that were as low as a 20% above the baseline HR with high sensitivity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations